2022
DOI: 10.1002/csc2.20796
|View full text |Cite
|
Sign up to set email alerts
|

Guar resilience in water‐restricted production

Abstract: Guar [Cyamopsis tetragonoloba (L.) Taub] is an alternative crop in the Southern High Plains that thrives in semi-arid regions, due to its low water input requirements. Field experiments were conducted in 2017 and 2018 at New Deal, TX, to evaluate the response of guar ('Matador') to four levels of deficit irrigation (DI; extreme, 51 mm; severe, 127 mm; moderate, 203 mm; and mild, 279 mm). Soil moisture extraction patterns, plant height, leaf area index, yield components, seed yield, harvest index (HI), agronomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…In general, growth parameters such as plant height and above-ground dry biomass at maturity were higher under the normal irrigation (I 1 ) regime, where no stress was experienced by guar plants, as compared to the reduced irrigation regimes (I 2 , I 3 , and I 4 ) (Table 1). These results are in accordance with previous studies that reported similar results [19,40]. It is interesting to note that although the irrigation regimes differed in imposing water stress during the reproductive stage, the water stress impacted plant height and above-ground biomass.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, growth parameters such as plant height and above-ground dry biomass at maturity were higher under the normal irrigation (I 1 ) regime, where no stress was experienced by guar plants, as compared to the reduced irrigation regimes (I 2 , I 3 , and I 4 ) (Table 1). These results are in accordance with previous studies that reported similar results [19,40]. It is interesting to note that although the irrigation regimes differed in imposing water stress during the reproductive stage, the water stress impacted plant height and above-ground biomass.…”
Section: Discussionsupporting
confidence: 93%
“…Due to its potential as an alternative crop in the Southwest US and a renewed interest in guar production, research on various aspects of guar production has recently gained impetus in the Southwest US [9][10][11][12][13][14][15][16][17]. A few recent studies have focused on the response of guar to irrigation level and shown the adaptability of guar under deficit irrigation conditions [18,19]. However, no studies have looked at deficit irrigation impacts on guar in the study region in combination with soil amendments such as biogenic silica in the region.…”
Section: Introductionmentioning
confidence: 99%